An organic hole-transporting material spiro-OMeTAD doped with a Mn complex for efficient perovskite solar cells with high conversion efficiency. Issue 52 (5th October 2021) - Elawad, Mohammed; John, Kingsley Igenepo; Idris, Ahmed Mahmoud; Yang, Li; Gao, Yuan
Abstract : Mesoscopic PSCs utilizing spiro-OMeTAD with different concentrations of a Mn complex were obtained, and the PSC with the optimum Mn-complex concentration (1.0% w/w) achieved a remarkable power conversion efficiency of 17.62%. Abstract : 2, 2′, 7, 7′-Tetrakis( N, N -di- p -methoxyphenylamine)-9, 9′-spiro-bi-fluorene(spiro-OMeTAD) has often been used as a hole-transporting material (HTM) in mesoscopic perovskite solar cells (PSCs). However, its potential applications are limited due to its poor conductivity of approximately 10 −6 to 10 −5 cm 2 V s −1 in pristine form, and this influences the stability and intrinsic hole conductivity of the device. In this work, a Mn complex [(Mn(Me-tpen)(ClO4 )2 − )] 2+ is introduced as a p-dopant to improve the properties of spiro-OMeTAD-based PSCs, including the optical, electrical, conductivity, and stability properties. Interestingly, the use of spiro-OMeTAD with an optimum concentration (1.0% w/w) of Mn complex in mesoscopic PSCs achieves a remarkable power conversion efficiency of 17.62% with a high conductivity of 99.05%. Spiro-OMeTAD with Mn complex as a p-dopant under UV-vis spectroscopy shows a different peak at 520 nm, confirming that oxidation occurs upon the addition of the Mn complex. The enhanced efficiency of the PSCs may be attributed to an increase in the optical and electrical properties of the HTM in the spiro-OMeTAD doped Mn complex.